Combination of phytoremediation technology of apu-apu plants (Pistia stratiotes) and blood cockle shell biofilters (Anadara granosa) in the processing of aquaculture waste - Nidya Kartini; Putu Cinthia Delis; Rizha Bery Putriani; Septi Malidda Eka Putri (Universitas Malikussaleh, 2026)
Aquaculture activities with high stocking densities will produce liquid and solid waste from fisheries cultivation which mostly contain organic materials, high levels of turbidity, and suspended solids. This study aims to measure the effectiveness of the apu-apu aquatic plant as a phytoremediator and blood cockle shell biofilter in processing organic waste from aquaculture to improve the water quality of fish farming ponds so that it can reduce waste levels. This study used a Completely Randomized Design (CRD) with two factors, namely the treatment of apu-apu plant density and observation time. Observations were carried out with three treatments and three replications. The main parameters measured were water quality which included temperature, pH, dissolved oxygen (DO), nitrate, ammonia, and phosphate levels. Observations of aquatic plants were in the form of measuring the leaf width and leaf weight of the apu-apu plant. Data analysis used ANOVA (Analysis of Variance). If there were influential variables, a further Duncan test was carried out with a significance level of 5%. The results showed that the combination treatment of apu-apu plants and mussel shells with a density of 10 clumps of apu-apu plants was more effective in reducing nutrient levels (phosphate); and 5 clumps to reduce nitrate levels during the 30-day phytoremediation process. The t-test results showed no significant difference in plant weight gain and apu-apu plant weight between treatments P1 and P2 (p<0.05). This indicates that both treatments had similar effects on apu-apu plant weight growth. Keywords: Apu-apu; Biofilter; Phytoremediation; Water Quality; Wastewater Treatment